Analisis Postur Kerja Menggunakan Metode Rapid Upper Limb Assessment (RULA) pada Bilik Las SMAW - Novitrie, Nora Amelia; Rachmat, Aulia Nadia; Firdausy, Ainur Rafika (Journal of Research and Technology, 2024)
Politeknik Perkapalan Negeri Surabaya (PPNS) is a vocational training institution that focuses on shipping and marine affairs. Through its education and training programs, PPNS provides in-depth knowledge of transportation engineering, including welding techniques. Welding plays an essential role in connecting and strengthening ship structures in the marine industry. However, welding can lead to the risk of occupational musculoskeletal disorders. This research describes the ergonomical hazards that may arise in PPNS welding operations. The causes of those are repetitive hand and arm movements and poor posture. Therefore, the purpose of this research is to identify occupational musculoskeletal hazards in the PPNS work environment and provide a basis for changes in workplace design to reduce these risks. The purpose of this study is to determine the possible risk of ergonomics by using GOTRAK and RULA for students who perform welding operations in the PPNS welding workshop through work practice. The research shown that the final score of RULA is 7 (high risk), which means it needs to be redesign.